1996
DOI: 10.1177/104990919601300509
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing volunteer effectiveness: A didactic and experiential workshop

Abstract: Presented is an actual workshop to enhance the personal and professional development of volunteers and their relationship with others. This workshop is a follow up to information in the article, "Enhancing volunteer effectiveness" which appeared in the May/june (1996) issue of The American Journal of Hospice & Palliative Care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The success of the training program can be attributed to the didactic and experiential approach [31,48,49], which consists of four essential elements in this study. First, the three-day intensive workshop gave the peer counselors the common base of knowledge and skills that they applied during the two-day practical training in the community.…”
Section: Discussionmentioning
confidence: 99%
“…The success of the training program can be attributed to the didactic and experiential approach [31,48,49], which consists of four essential elements in this study. First, the three-day intensive workshop gave the peer counselors the common base of knowledge and skills that they applied during the two-day practical training in the community.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has identified the importance of using metaphors to explain and communicate experiences in hospice volunteer training and recruitment (Gilstrap & White, 2013; Sexton, 1997). To date, however, communication training for hospice volunteers has largely focused on communication with patients, family, and hospice staff (Hall & Marshall, 1996). This study underscores the importance of supplementing internal-based communication training with external-based communication training to help volunteers proactively voice common, role-based experiences to outside audiences.…”
Section: Discussionmentioning
confidence: 99%
“…Hall and Marshall [5] discuss the importance of creating for volunteers a 'risk free environment' and the learning environment being 'a safe zone'. Being more prescriptive in the role-play scenarios, with more group discussions prior to each regarding possible outcomes and workshopping ways of responding using supportive communication skills outlined in the training programme content, may result in less anxiety for future participants.…”
Section: Discussionmentioning
confidence: 99%